2019
DOI: 10.1016/j.virusres.2019.197730
|View full text |Cite
|
Sign up to set email alerts
|

Proteases facilitate the endosomal escape of porcine epidemic diarrhea virus during entry into host cells

Abstract: A B S T R A C TExogenous and endogenous proteases play important roles in porcine epidemic diarrhea virus (PEDV) entry and replication. The roles of proteases in the viral endosomal escape and replication using trypsin (KD) or elastase (AA)-adapted US PEDV strains were studied. While PEDV KD and AA require different exogenous protease for efficient replication in cells, PEDV KD was more dependent on the protease than PEDV AA. There was no marked difference in viral trafficking between them during the entry eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The S protein of PEDV was activated by endo-lysosomal cysteine proteases, such as CTSL and CTSB, to expose a fusion domain for membrane fusion and viral genome translocation to the cytoplasm [ 5 , 6 ]. CTSL and CTSB require low pH for their optimal activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The S protein of PEDV was activated by endo-lysosomal cysteine proteases, such as CTSL and CTSB, to expose a fusion domain for membrane fusion and viral genome translocation to the cytoplasm [ 5 , 6 ]. CTSL and CTSB require low pH for their optimal activity.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, the viral genome is released into the cytoplasm [4]. During the entry process, Cathepsin L (CTSL) and Cathepsin B Pathogens 2023, 12, 845 2 of 15 (CTSB), two types of endo-lysosomal enzymes, are required to alter the conformation of the PEDV-S to activate membrane fusion [5,6]. Some previous studies have indicated that the maximal activity of CTSL and CTSB requires endo-lysosomes to have a highly acidic pH [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…In summary, although pAPN may not function as a receptor for PEDV, it enhances viral replication and proliferation through a synergistic effect with an as-yet-unidentified receptor ( Shirato et al, 2016 ). Moreover, the presence of trypsin enhances the synergistic effect between pAPN and its receptors, promoting the replication and proliferation of PEDV ( Oh et al, 2019 ). Trypsin is a serine endopeptidase that has been widely studied with respect to the cleavage and activation mechanisms of viral glycoproteins.…”
Section: Interaction Between S Protein and Host Proteinmentioning
confidence: 99%
“…According to the current research results, there are two ways for CoVs to invade cells; one is endocytosis. Viral S protein interacts with receptor and then virus particles are wrapped in endosomes to enter host cells [ 72 ]. In endosomes, the viral envelope and membrane structure of endosomes are fused in the environment of cathepsin L (CTSL) and low pH to release the viral genome into the host cytoplasm [ 73 ].…”
Section: Secov Infection and The Involvement Of Host Factorsmentioning
confidence: 99%